Matrix Ranking: A Tool for Decision-Making and Prioritization - Keegan Gay; Eric Stubbs; Sebastian Galindo-Gonzalez (EDIS, 2016)
Matrix ranking is an activity used to analyze and prioritize information. Extension professionals often work with community groups who may benefit from this type of analysis. This 4-page fact sheet explains how Extension professionals can use matrix ranking to facilitate prioritization and decision-making. Written by Keegan Gay, Eric Stubbs, and Sebastian Galindo-Gonzalez, and published by the Department of Agricultural Education and Communication, October 2016.